Mapping interventional cardiology in Europe: the European Association of Percutaneous Cardiovascular Interventions (EAPCI) Atlas Project. (25th June 2020) - Barbato, Emanuele; Noc, Marko; Baumbach, Andreas; Dudek, Dariusz; Bunc, Matjaz; Skalidis, Emmanouil; Banning, Adrian; Legutko, Jacek; Witt, Nils; Pan, Manuel; Tilsted, Hans-Henrik; Nef, Holger; et al.
Abstract: Aims: The European Association of Percutaneous Cardiovascular Interventions (EAPCI) Atlas of Interventional Cardiology has been developed to map interventional practice across European Society of Cardiology (ESC) member countries. Here we present the main findings of a 16-country survey in which we examine the national availability of interventional infrastructure, human resource, and procedure volumes. Methods and results: Sixteen ESC member countries participated in the EAPCI Atlas survey. Interventional data were collected by the National Cardiac Society of each participating country. An annual median of 5131 [interquartile range (IQR) 4013–5801] diagnostic heart procedures per million people were reported, ranging from <2500 in Egypt and Romania to >7000 in Turkey and Germany. Procedure rates showed significant correlation ( r = 0.67, P = 0.013) with gross national income (GNI) per capita. An annual median of 2478 (IQR 1690–2633) percutaneous coronary interventions (PCIs) per million people were reported, ranging from <1000 in Egypt and Romania to >3000 in Switzerland, Poland, and Germany. Procedure rates showed significant correlation with GNI per capita ( r = 0.62, P = 0.014). An annual median of 48.2 (IQR 29.1–105.2) transcatheter aortic valve implantation procedures per million people were performed, varying from <25 per million people in Egypt, Romania, Turkey, and Poland to >100 per million people in Denmark, France, Switzerland, and Germany. Procedure rates showed significant correlation with national GNI per capita ( r = 0.92, P < 0.001). Conclusion: The first report from the EAPCI Atlas has shown considerable international heterogeneity in interventional cardiology procedure volumes. The heterogeneity showed association with national economic resource, a reflection no doubt of the technological costs of developing an interventional cardiology service. Graphical Abstract: